2017
DOI: 10.4025/jphyseduc.v28i1.2803
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Between Instruments for Assessment of Body Balance in Active Elderly Individuals

Abstract: RESUMOO objetivo do estudo foi analisar a correlação entre instrumentos utilizados à avaliação do equilíbrio corporal e a predição do risco de quedas de idosos ativos. Estudo transversal, observacional, realizado com 41 mulheres (69,24±5,24 anos) praticantes de exercícios físicos, em Petrolina-PE. Os instrumentos utilizados foram a Escala de Equilíbrio de Berg (EEB), o Índice de Marcha Dinâmica (DGI), o "Timed Up and Go" simples (TUG), o "Timed Up and Go" motor (TUGm), o "Timed Up and Go" cognitivo (TUGc) e o … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this Integrative Review, it was found that the application of the Berg Scale was varied, however, there was a predominance of execution in the community (18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,33,34,35,36,37,38,39,40,41,42), coexistence center (18,19,31,34), school clinic of Physical Therapy in the community (20,24,29,30,33), Primary Health Care.…”
Section: Berg-bse Balance Scale;mentioning
confidence: 99%
See 1 more Smart Citation
“…In this Integrative Review, it was found that the application of the Berg Scale was varied, however, there was a predominance of execution in the community (18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,33,34,35,36,37,38,39,40,41,42), coexistence center (18,19,31,34), school clinic of Physical Therapy in the community (20,24,29,30,33), Primary Health Care.…”
Section: Berg-bse Balance Scale;mentioning
confidence: 99%
“…The Berg Scale classified the condition of functional balance as safe for the groups that practice physical activity and do not practice physical activity (18,19,21,28,31,32). Furthermore, the calculated relative risk was 0.2, demonstrating that the practice of ballroom dancing is expressed as a protection factor for the Berg Scale lower than 45 (23).…”
Section: Berg-bse Balance Scale;mentioning
confidence: 99%
“…This correlation shows the need to evaluate factors that detect balance deficits and risk of falls in the elderly. 60 Other instruments with greater evidence for this IR were observed, such as the Berg Balance Scale (BSE), used to assess the functional capacity of balance in the elderly 61 and the Time to Go Test (TUG) effective to reveal individuals at greater risk of falls, 62 the TUG emerges as an essential instrument to delimit the appropriate treatment for the improvement of the balance. 63 As well as the efficacy of BSE in relation to the evaluation of the balance in situations of the individual's daily life using few resources for his application.…”
Section: Lilacsmentioning
confidence: 99%